2020
DOI: 10.1136/bmjresp-2019-000449
|View full text |Cite
|
Sign up to set email alerts
|

Complications and discomfort after research bronchoscopy in the MicroCOPD study

Abstract: background Data on discomfort and complications from research bronchoscopy in chronic obstructive pulmonary disease (COPD) and asthma is limited. We present complications and discomfort occurring within a week after bronchoscopy, and investigate personal and procedural risk factors. Methods 239 subjects with COPD, asthma or without lung disease underwent research bronchoscopies as part of a microbiome study of the lower airways (the MicroCOPD study). Bronchoscopy was done in the supine position with oral scope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Hypoxia is the most commonly cited adverse event in patients undergoing bronchoscopy [16,17,28]. The occurrence of hypoxemia was highly prevalent during FB in our study, with an oxygen saturation of < 90% for ≥ 5 s measured in 132 patients (91%).…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…Hypoxia is the most commonly cited adverse event in patients undergoing bronchoscopy [16,17,28]. The occurrence of hypoxemia was highly prevalent during FB in our study, with an oxygen saturation of < 90% for ≥ 5 s measured in 132 patients (91%).…”
Section: Discussionmentioning
confidence: 58%
“…Nonetheless, the occurrence of hypoxemia during flexible bronchoscopy with sedation is similar in studies with and without supplemental oxygen [16,[33][34][35]. A recent study in Norway has shown that when patients chose to have no sedation, it significantly increased unplanned interventions during the bronchoscopy [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While research protocols often involve performing bronchoscopy on healthy volunteers without underlying lung disease, to investigate the pathophysiology it is often necessary to obtain clinical samples via BAL from human subjects with underlying lung disease. A recent study investigated the safety of research bronchoscopy in patients with COPD and asthma [ 30 ]. The results of this study include safety data of bronchsocopy with BAL as well as protected brush sampling and endobronchial biopsies.…”
Section: Discussionmentioning
confidence: 99%
“…To justify an elective invasive procedure for research with no direct clinical benefit the risks need to be minimal. Recent studies have evaluated the risk of research bronchoscopy in patients with COPD and asthma [ 30 , 31 ], however little is known about the risks of research bronchoscopy in adults with CF. We report here the outcomes of our single-institution research bronchoscopy program on CF and non-CF volunteers with an excellent safety profile.…”
Section: Introductionmentioning
confidence: 99%